2021
DOI: 10.3390/geriatrics6040117
|View full text |Cite
|
Sign up to set email alerts
|

Can RUDAS Be an Alternate Test for Detecting Mild Cognitive Impairment in Older Adults, Thailand?

Abstract: The Montreal Cognitive Assessment (MoCA) is the commonly used cognitive test for detecting mild cognitive impairment (MCI) in Thailand. Nevertheless, cultural biases and educational levels influence its performance. The Rowland Universal Dementia Assessment Scale (RUDAS) seems to lower the limitation of the MoCA. This study aimed to compare the performance of the RUDAS and the MoCA for the diagnosis of MCI and demonstrate the correlation between them. A cross-sectional study of 150 older participants from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In another study, native English speakers outperformed non‐native English speakers on several neuropsychological tests, 10 suggesting that delivering tasks in a non‐native language might negatively impact test performance. Similar observations have been reported for many other populations with diverse linguistic abilities, leading to the development of different language‐specific versions of these neuropsychological tests 11–17 . In this context, a plain translation of such tests might not be enough, that is, the transcripted word in another language might have a slightly different conceptual meaning and can bias test results.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…In another study, native English speakers outperformed non‐native English speakers on several neuropsychological tests, 10 suggesting that delivering tasks in a non‐native language might negatively impact test performance. Similar observations have been reported for many other populations with diverse linguistic abilities, leading to the development of different language‐specific versions of these neuropsychological tests 11–17 . In this context, a plain translation of such tests might not be enough, that is, the transcripted word in another language might have a slightly different conceptual meaning and can bias test results.…”
Section: Introductionsupporting
confidence: 72%
“…Similar observations have been reported for many other populations with diverse linguistic abilities, leading to the development of different language‐specific versions of these neuropsychological tests. 11 , 12 , 13 , 14 , 15 , 16 , 17 In this context, a plain translation of such tests might not be enough, that is, the transcripted word in another language might have a slightly different conceptual meaning and can bias test results. Thus, administering these translated versions to speakers of understudied languages might pose a real challenge to health‐care professionals to generate clinically useful scores, particularly when the diagnosis is based on comparing measured scores to prior cut‐off values.…”
Section: Introductionmentioning
confidence: 99%
“…One is that the prior study used the modified MINI-COG-PS to detect cognitive impairment, while we used the Thai version of the MoCA, which may have a higher sensitivity for detecting cognitive impairment in older patients. Prior studies conducted in Srinagarind Hospital found that a MoCA score < 20 can diagnose MCI in an outpatient population with 76.2% sensitivity and 71.3% specificity, while the Mini-COG provided only 69% sensitivity and 73% specificity [ 32 , 37 ]. Another possible reason for this discrepancy may be the differences in the studied populations.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, the Thai version of Montreal Cognitive Assessment test (MoCA-T) was used to evaluate the participants’ cognitive status. A previous study conducted at the Internal Medicine outpatient clinic of Srinagarind Hospital revealed that a MoCA-T score < 20 was an appropriate cut-off point to indicate MCI in older patients in this setting, with a sensitivity of 0.76 and specificity of 0.71 [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Universal cut-offs can also lead to sampling biases, whereby a cut-off may not match with the individuals being assessed [ 25 ] (e.g., if a target population has a lower level of education or higher rates of illiteracy). As such, this could lead to false conclusions made about an individual’s cognitive ability which could have certain consequences, such as leading to inaccurate diagnosis.…”
Section: Introductionmentioning
confidence: 99%